Cultural capacity, self-efficacy, and humility of healthcare providers: a survey in Southeast Iran - Shima Gadari; Somayeh Jouparinejad; Sara Noori Farsangi; Amirreza Sabzi; Aida Jafari; Jamileh Farokhzadian (BMC Primary Care)
Abstract Background With the increasing cultural diversity in healthcare settings, it is essential for healthcare providers to possess the three key characteristics of cultural capacity, self-efficacy, and humility in order to deliver optimal and culturally congruent care. The present study aimed to assess the relationship between cultural capacity, self-efficacy, and humility among healthcare providers. Method This cross-sectional study used a convenience sampling method to include 203 healthcare providers from comprehensive health centers and facilities affiliated with Kerman University of Medical Sciences in Kerman, southeastern Iran. Data were collected through a demographic information questionnaire, the Cultural Capacity Scale Arabic (CCS-A), the Cultural Self-Efficacy Scale (CSES), and the Foronda’s Cultural Humility Scale. Results The results indicated that healthcare providers exhibited a moderate level of cultural capacity (60.38 ± 19.12) and cultural self-efficacy (60.29 ± 19.39), and occasionally demonstrated cultural humility (60.22 ± 11.43). Furthermore, cultural capacity showed a direct and significant correlation with both self-efficacy and cultural humility (P < 0.001). Additionally, cultural humility exhibited a direct and significant correlation with cultural self-efficacy (P < 0.001). Academic degree (β = 0.13, p = 0.005), education outside of place of residence (β = 0.1, p = 0.02), attendance in cultural care training (β = 0.21, p = 0.01), self-efficacy (β = 0.56, p = 0.001), and cultural humility (β = 0.11, p = 0.001) were significant predictors of the cultural capacity. Conclusion The results suggested that the cultural capacity, self-efficacy, and humility of healthcare providers were at a moderate level, and these variables were interrelated. Given that cultural capacity, competence, and humility are fundamental concepts in addressing ethnic and cultural diversity in societies, healthcare policymakers should strive to improve the levels of these important cultural attributes and develop strategies to enhance these qualities in healthcare providers.